The positional arms race in higher education - Gordon C. Winston (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2000)
The market for undergraduate education has many similarities to an arms race. A school's position - relative to other schools - determines its success in attracting students and student quality. Its position, in turn, is largely determined by the size of its student subsidies, the difference between its educational spending and the net tuition it charges its students (or, much the same thing, how much their students have to pay for a dollar's worth of educational spending). High-subsidy schools spend the most per dollar of tuition so that 'bargain' attracts the highest quality students. To change its position, a school must spend more or charge less - and find the resources to support it. The positional arms race suggests why competition from a school further down in the hierarchy forces a response more effectively than competition from above and why it's been typical of higher education that costs rise to reposition, but prices don't fall.
Keywords: 330; Studium; Subvention; Studienfinanzierung; Wettbewerb; USA